Improvement of semantic processing ability of Chinese characters in school children: A comparative study based on 2009 and 2019 data - Zhang, Qinfen; Dong, Xuan; Song, Yan; Wang, Chaoqun; Ji, Shiyan; Mei, Haitian; Wang, Rui (Frontiers in Neuroscience, 2023)
To explore the characteristics of semantic cognitive development of school children by observing the development changes over 10 years, a retrospective event-related potential (ERP) study was conducted on the semantic processing characteristics of Chinese characters in children aged 7–11 years with the same study design in 2009 and 2019. For the EEGs recorded in 2009, the N400 amplitude of semantic processing in children aged 7–11 years showed an approximately inverted U-shaped development trend with a slow rise at the age of 7–9, a peak at the age of 10, then a rapid decline at the age of 11. However, for the EEGs recorded in 2019, the N400 amplitude showed a gradually decreasing development trend with a slow decline for the 7–11 years class. Our data suggested that the semantic processing of Chinese characters in children aged 7–11 years in 2019 was one age stage earlier than that in 2009. The children’s brain cognition is in the process of development and change with high plasticity. 10 years of favorable social and educational environmental factors have significantly improved children’s semantic processing ability of Chinese characters.